Quinoline Derivatives Kill Mycobacterium tuberculosis by Activating Glutamate Kinase. Issue 8 (15th August 2019) - Makafe, Gaelle G.; Hussain, Muzammal; Surineni, Goverdhan; Tan, Yaoju; Wong, Nai-Kei; Julius, Mugweru; Liu, Lanying; Gift, Chiwala; Jiang, Huofeng; Tang, Yunxiang; Liu, Jianxiong; Tan, Shouyong; et al.
Summary: There is a great need for identification and development of new anti-tuberculosis drugs with novel targets. Recent drug-discovery efforts typically focus on identifying inhibitors but not activators that perturb metabolic enzymes' functions as a means to kill Mycobacterium tuberculosis (Mtb). Here, we describe a class of quinoline compounds, Z0933/Z0930, which kill Mtb by acting as activators of glutamate kinase (GK), a previously untargeted enzyme catalyzing the first step of proline biosynthesis. We further show that Z0933/Z0930 augment proline production and induce Mtb killing via proline-derived redox imbalance and production of reactive oxygen species. This work highlights the effectiveness of gain-of-function probes against Mtb and provides a framework for the discovery of next-generation allosteric activators of GK. Graphical Abstract: Highlights: Identification of glutamate kinase (GK) as new anti-tuberculosis drug target Identification of Z0933/Z0930 as GK allosteric activators Induction of proline and reactive oxygen species overproduction for cell death Small-molecule-induced enzyme activation as drug-development strategy against Mtb Abstract : Makafe et al. identified glutamate kinase (GK) as a new anti-tuberculosis drug target. Small-molecule-induced GK activation killed Mycobacterium tuberculosis (Mtb) via induction of proline and reactive oxygen species overproduction. This work highlights the effectiveness of enzyme activation, rather than inhibition, as a potential drug-development strategy against Mtb.